The Effect of Shopping Lifestyle, Influencers, and Price Discounts on Impulse Buying on Tiktok Shop - Manap, Abdul; Pujadi, Arko; Chandra, Betari Kilisuci Kartika; Agung, Mohamad Ramadhan (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to determine the effect of shopping lifestyle, influencers and price discounts on impulse buying at TikTok shops in Depok. This study uses a quantitative method and uses a Likert scale as a measurement. The population in this study were all consumers in Depok who had made impulsive purchases through TikTok shops. The research sample consisted of 120 respondents. Data collection was carried out by distributing questionnaires via Google Forms. Data testing used validity tests, reliability tests, classical assumption tests, multiple linear regression tests, hypothesis tests and determination tests with the help of SPSS 24 software. The results of this study indicate that shopping lifestyle partially has no effect on impulse buying at TikTok shops in Depok, Influencers and price discounts have a positive and significant effect on impulse buying at TikTok shops in Depok, West Java.